Comparative study on sustainable agriculture knowledge among Malaysia contract farmers - Azman, Azmariana; D’Silva, Jeffrey Lawrence; Abu Samah, Bahaman; Man, Norsida; Mohamed Shaffril, Hayrol Azril (Science Publications, 2012)
Problem statement: Modern farming methods like contract farming must emphasize on the need to practice sustainable agriculture so that it will lead towards the development of the agriculture sector. To do so, knowledge is paramount as this will enable the implementation of good agriculture practices. What is the current level of knowledge of contract farmers with regards to sustainable agriculture? Is there any difference in the level of knowledge between farmers from different zones? Thus, this study would like to investigate on the level of knowledge pertaining to sustainable agriculture practices between contract farmers from east and west Malaysian. Approach: This study used a survey methodology to obtain the data. A total of 160 respondents participated in the study and the data was analyzed using the SPSS software. Results: From the result, it was identified that the respondents were at a high level pertaining to their knowledge on sustainable agriculture. Further analysis showed that there is a significant difference in knowledge based on different zones. Conclusion: The study recommends that more efforts should be taken by respective stakeholders to further improve farmers’ knowledge regarding pest control, soil erosion and proper usage of machine for agriculture.